Investigating the Mental Health Impacts of University Campus Green Space Through Perceived Sensory Dimensions and the Mediation Effects of Perceived Restorativeness on Restoration Experience - Malekinezhad, Fahimeh; Courtney, Paul; bin Lamit, Hasanuddin; Vigani, Mauro (Frontiers in Public Health, 2020)
Introduction: Green spaces support people mentally in their everyday life. Perceived restorativeness and Perceived Sensory Dimension (PSD) have been addressed as optimal environmental related characteristics with regards to psychological restoration. However, relatively little research has investigated how the perception of these characteristics, directly and indirectly, affects restoration experience, particularly in a sample of university students within the area of green outdoor campus landscapes. Methods: This study hypothesizes these associations through application of partial least squares structural equation modeling (PLS-SEM), inputting data from a sample of university students in Malaysia. In the hypothesized model, we examine the degree of restoration that is enjoyed by subjects within landscapes through the effects of these characteristics. Indirect effects of perceived restorativeness via evaluation of mediation effects associated with perception of landscape characteristics and restoration experience are also investigated. Results: Through validation of the measurement model, we find significant positive coefficient paths with adequate predictive abilities in the hypothesized model. Findings suggest the effect of PSD on perceived restorativeness leads to a better explanation of restoration experience. In addition, perceived landscape characteristics of PSD enhance restoration experience in alignment with perceived restorativeness characteristics. Conclusions: Greater effects on restoration experience come through perceived restorativeness that is affected by PSD, which itself is capable of promoting favorable experiences of restorativeness in a green space and facilitating psychological restorative outcomes. The mechanistic effect of emotional regulation implies a distinct role of green spaces in maintaining good mental health and has relevance to public health models that promote independence and well-being through preventative approaches. The work paves the way for further studies that examine which dimensions of PSD support perceived restorativeness and restoration experience more than others, and the wider psycho-social value of green spaces through the application of mediation effects and personal sensory dimensions in the development of mental health.